Roof top rainwater collection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
A civil engineer explains how low-cost guttering and ponds can enable a family to harvest significant quantities of water from their roof.